The growth of waqf properties through infrastructure development according to al-hadith - Yaakob, Mohd Ashrof Zaki; Suliaman, Ishak; Khalid, Mohammad Mahyuddin (Universiti Putra Malaysia, 2017)
Waqf is an Islamic institution to serve as a catalyst for Muslim economic development. The existence of this socio-economic institution started with Prophet Muhammad (pbuh) and it became the root of success for the Islamic social security system. The expansion of waqf properties through investment or istithmar is e one of the possible ways to utilise waqf. It was found that 75% of the hadith related to waqf in al-Kutub al-Sittah debated on waqf infrastructure. This shows the importance of infrastructure development in the expansion of waqf properties.